Elevated Circulating IL-10 Producing Breg, but Not Regulatory B Cell Levels, Restrain Antibody-Mediated Rejection After Kidney Transplantation - Luo, Yongsheng; Luo, Feifei; Zhang, Kuanxin; Wang, Shilei; Zhang, Haojie; Yang, Xianlei; Shang, Wenjun; Wang, Junxiang; Wang, Zhigang; Pang, Xinlu; Feng, Yonghua; Liu, Lei; et al. (Frontiers in Immunology, 2021)
Background Antibody-mediated rejection (AMR) occupies a major position for chronic rejection after kidney transplantation. Regulatory B cell (Breg) has been reported to have an inhibitory immune function, which contributes to the resistance for AMR. Methods A nested case–control study for nine healthy donors, 25 stable (ST) patients, and 18 AMR patients was performed to determine the type of Breg in maintaining immune tolerance and preventing AMR. Results Compared to the ST group, circulating interleukin (IL)-10+ Bregs, but not Bregs, significantly decreased. The receiver operating characteristic (ROC) curve analysis revealed that rather than the circulating Bregs, decreased circulating IL-10+ Breg levels were positively associated with AMR. However, kidney B cell and IL-10 infiltration was significantly increased in the AMR group with high expression of C-X-C motif chemokine 13 (CXCL13). In addition, circulating IL-10+ Bregs, rather than Bregs, remained higher than those at pre-operation, during the 90-day post-operation in immune homeostasis. Conclusion The circulating IL-10+ Breg levels are more appropriate measures for assessing the resistance of AMR after kidney transplantation.